Political Defections in Nigeria: Implications for Our Nascent Democracy (Texas Journal of Multidisciplinary Studies, 2022)
The Nigerian political turf is replete with a monstrous phenomenon which has emerged as a potent retrogressive factor with the capability of torpedoing our nascent democracy. This sinister offshoot of our democratic experience is the fanciful multi-numenclated phenomenon called Political Defection. The prime focus of this discourse is to undertake a philosophical expository analysis of the conversational narratives bordering on the subject under investigation. In this essay, therefore, a historical exposition of particular cases of cross-carpeting as well as a corresponding analysis of the causes, legitimacy and implications of political porting will be surveyed. The essay will also discuss the possible ways of curbing incessant party switching so as to strengthen and foster the deepening of democracy in Nigeria.